2010
DOI: 10.1089/scd.2009.0142
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming of Somatic Cells After Fusion With Induced Pluripotent Stem Cells and Nuclear Transfer Embryonic Stem Cells

Abstract: In this study we examine whether a somatic cell, once returned to a pluripotent state, gains the ability to reprogram other somatic cells. We reprogrammed mouse embryonic fibroblasts by viral induction of oct4, sox2, c-myc, and klf-4 genes. Upon fusion of the resulting iPS cells with somatic cells harboring an Oct4-GFP transgene we observed, GFP expression along with activation of Oct4 from the somatic genome, expression of key pluripotency genes, and positive immunostaining for Oct4, SSEA-1, and alkaline phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 28 publications
0
16
0
1
Order By: Relevance
“…It has previously been shown that both mouse iPS (Maherali et al, 2007;Sumer et al, 2010a) and SCNT derived ntES cells somatic cell hybrids is high and similar to those of ES cells (Cowan et al, 2005;Sumer et al, 2010b), and may be the underlying mechanism for the lengthening of the somatic cell derived chromosomes telomeres in hybrids (Sumer et al, 2010b). Telomere repeat amplification protocol (TRAP) assay was conducted on cell lysates from equal number of cells in order to determine the levels of telomerase activity of the various cell lines (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has previously been shown that both mouse iPS (Maherali et al, 2007;Sumer et al, 2010a) and SCNT derived ntES cells somatic cell hybrids is high and similar to those of ES cells (Cowan et al, 2005;Sumer et al, 2010b), and may be the underlying mechanism for the lengthening of the somatic cell derived chromosomes telomeres in hybrids (Sumer et al, 2010b). Telomere repeat amplification protocol (TRAP) assay was conducted on cell lysates from equal number of cells in order to determine the levels of telomerase activity of the various cell lines (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…R, GGTTGTTGCCCTCATCTCTCT (Sumer et al, 2010a), like ES cells, have the ability to reprogram a somatic genome following cell fusion. In the present study we have shown that iPS cells are as efficient as ES cells at reprogramming somatic cells by cell fusion.…”
Section: Rt-pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…This is echoed by recent experiments: somatic cells, when fused with pluripotent cells (either ESCs or iPSCs) always produce binucleate cells with both nuclei in a pluripotent state (Sumer et al, 2009). Furthermore, induced pluripotency has been demonstrated at extremely low (0.006%) efficiencies through the use of recombinant pluripotent factors with multiple treatments over an 8-week period.…”
Section: Direct Treatment With Pluripotency Factorsmentioning
confidence: 99%
“…Fusing somatic cells with stem cells allows the resulting hybrid cells to be reprogrammed as stem cell-like cells. Recently, hybrid cells derived from stem cells have been proven to be reprogrammable into ES cell-like cells in vitro [14][15][16][17][18][19][20]. They are pluripotent and are capable of contributing to cells from all three germ lines.…”
Section: Introductionmentioning
confidence: 99%